Intrinsically stretchable fully π-conjugated polymers with inter-aggregate capillary interaction for deep-blue flexible inkjet-printed light-emitting diodes - Mingjian Ni; Zhiqiang Zhuo; Bin Liu; Xu Han; Jing Yang; Lili Sun; Yuekuan Yang; Jiangli Cai; Xiang An; Lubing Bai; Man Xu; Jinyi Lin; et al. (Nature Communications)
Abstract Fully π-conjugated polymers consisting of plane and rigid aromatic units present a fantastic optoelectronic property, a promising candidate for printed and flexible optoelectronic devices. However, obtaining high-performance conjugated polymers with an excellent intrinsically flexible and printable capacity is a great challenge due to their inherent coffee-ring effect and brittle properties. Here, we report an asymmetric substitution strategy to improve the printable and stretchable properties of deep-blue light-emitting conjugated polymers with a strong inter-aggregate capillary interaction for flexible printed polymer light-emitting diodes. The loose rod-shaped stacking of asymmetric conjugated polymers chain in the precursor printed ink makes it easier to improve the intrinsic stretchability of inkjet-printed films. More interestingly, the anisotropic shape rod-like aggregate of conjugated polymers chains also induced a strong capillary interaction and further suppressed the coffee-ring effect, which is more likely to allow for uniform deposition during printed processing and form uniform printed films.